Best practice in primary care pathology: review 8. Issue 7 (15th December 2006) - Smellie, W S A; Hampton, K K; Bowlees, R; Martin, S C; Shaw, N; Hoffman, J; Ng, J P; Mackenzie, S M; van Heyningen, C
Abstract : This eighth best practice review examines four series of common primary care questions in laboratory medicine: (i) sodium abnormalities; (ii) faecal occult blood testing; (iii) warfarin management; and (iv) sputum cytology in diagnosis of bronchopulmonary malignancy. The review is presented in question–answer format, referenced for each question series. The recommendations represent a précis of guidance found using a standardised literature search of national and international guidance notes, consensus statements, health policy documents and evidence-based medicine reviews, supplemented by Medline Embase searches to identify relevant primary research documents. They are not standards but form a guide to be set in the clinical context. Most are consensus rather than evidence-based. They will be updated periodically to take account of new information.